A PREVIEW OF ‘META-ANALYSIS’ QUANTITATIVE SYNTHESIS OF THE DIVERSE STATISTICAL RESEARCH RESULTS - P. K , SUDHIR.; H, VENKATESAN. (International Journal of Psychosocial Rehabilitation, 2020)
The Clinical Trials are being carried out across the world over various geographical areas, on diverse races & ethnics, on various economic groups, with different set of Samples, with Research Methodological differences, laden with different levels of Biases, etc., Often the Researches are repeated by different Researchers at different locations to confirm the previous Research results or to increase their precision & validity. But this Replication of the Researches is often quite difficult due to the above said diverse reasons. Subsequently thus obtained statistical results are also diverse and at times conflicting to each other. In spite of these difficulties integration of findings of different individual studies is much important. The judicious integration of analogous Research results excluding the insignificant deviations has a major role in establishing an ‘Evidence Based Medicine’. Meta-analysis is a technique used to systematically merge the findings of different independent studies, using rigorous statistical methods to calculate an ‘absolute’ effect. This review article is primarily aimed at exploring the rationale of the Scientific Methodology – Meta-analysis.